PPO.44 An analysis of activity and outcomes in the preterm surveillance clinic at the national maternity hospital. (9th June 2014) - Neville, G; Higgins, S
Abstract : Accurate identification of high risk groups and focused efforts at reducing their risk may be the most effective method currently available of reducing the incidence and associated squeale of preterm birth. A preterm surveillance clinic was established in March 2012 to provide expert management of those at risk of preterm birth. We aimed to establish the epidemiology, antenatal course and outcomes of those who attended this clinic in its first year of operation. In addition, trends in preterm delivery over the past 5 years in patients booked to attend NMH were reviewed. Prospectively collected records of all patients who attended the clinic and had an estimated delivery date between the 1st July 2012 and 30th June 2013 were included for analysis. Patterns in preterm delivery rates (broken down into six month periods) were analysed for the study duration and the 4 years prior to it. 54 patients of the clinic met the inclusion criteria. Attendees included those with a previous preterm birth, previous cervical surgery, known uterine anomaly and previous need for cervical suture. 75.59% (n = 41) progressed past a gestation of 34+0, 16.67% (n = 9) delivered between 24+0 and 33+6 weeks gestation and 7.41% (n = 4) suffered mid trimester losses (13+0–23+6). 91.7% (n = 11) of those who delivered preterm were having active intervention prior to delivery in contrast to 33.33% (n = 11) who progressed to term (>37+0 weeks). The overall incidence of preterm birth in our unit decreased since establishment of this clinic. We are effectively identifying those at highest risk of preterm delivery. Trends since establishment of the clinic show promising early evidence that effort at secondary management of preterm birth risk is positively impacting on the preterm birth rate in our institution.